(untitled) (Entrepreneurship Journal for Finance and Business, 2026)
The research aims to identify the role and procedures of external auditing in developing and enhancing the work of internal control in governmental institutions. It also seeks to determine the extent to which the adherence of government units to internal control components according to COSO contributes to strengthening their effectiveness. Furthermore, it explores the role of the external auditor in examining and evaluating internal control within governmental units and the extent to which external auditing relies on it. To achieve the research objective, questionnaire data were analyzed using statistical methods, specifically Factor Analysis, to determine the relative importance of each factor. Weighted data were then obtained based on the importance determined by factor analysis, followed by structural equation modeling (SEM) analysis, incorporating the mediator variable (internal control components according to COSO). The research population was defined as the Federal Board of Supreme Audit employees working in the Ministry of Electricity under the Iraqi Federal Financial Supervisory Board. The research sample was limited to a governmental unit subject to the audit of the research population, specifically the headquarters of the Iraqi Ministry of Electricity, due to the availability of the necessary data and their cooperation in scientific research. The theoretical part of the research relied on collecting data from books, articles, theses, dissertations, scientific studies, and all research related to the topic, whether in Arabic or English, as well as online resources. The practical part depended on creating a questionnaire distributed to the sample individuals. The research reached several conclusions, the most notable being the lack of awareness among government units and their staff, especially the sample, regarding professional publications related to internal control, such as international and local auditing standards. It also highlighted the failure to keep up with guidelines issued by the Federal Financial Supervisory Board (e.g., the 2007 Internal Audit Units Guidance Manual, Audit Manual No. 4, and the 2024 Internal Control Manual). This was confirmed by practical findings, where respondents agreed on the existence of a relationship and influence between external auditing and the effectiveness of internal control. This influence could be negative if external auditors fail to develop and update audit mechanisms. Additionally, relying on COSO internal control components in external auditing helps enhance the effectiveness of internal control, as shown by the analysis results, especially with the presence of the mediator variable. However, the lack of knowledge about these components has led to weak attention to internal control elements, ultimately weakening internal control in public sector units. Among the key recommendations of the research is the need to familiarize employees within the unit with professional publications related to internal control, particularly the 2024 Internal Control Manual issued by the Federal Financial Supervisory Board. This manual emphasizes the importance of adhering to internal control components and principles and their impact on enhancing the effectiveness of internal control. This can be achieved through seminars, workshops, and conferences conducted by specialists, in addition to those organized by the Federal Financial Supervisory Board. Furthermore, it is essential to distribute all professional publications related to internal control to employees for review and awareness of their key provisions.